On dying in a city gate: implications in the deaths of Eli, Abner and Jezebel - Quine, Cat (Journal for the study of the Old Testament, 2016)
Recent research has shown that city gates were a place of judgment, execution, and public displays in ancient Israel and the ancient Near East. This article explores the role of the gate on the literary level in the narratives concerning the deaths of Eli, Abner and Jezebel. It demonstrates how the function of gates in ancient Israel, and the institutions associated with them, allow the narrator to draw on themes of judgment, punishment and order, as well as creating a sense of irony throughout.